WATCHING THE ADVERSARY: EVALUATIONS OF A BRAZILIAN MILITARY ATTACH IN BUENOS AIRES (1914-1915) : Avaliações de um adido militar brasileiro em Buenos Aires (1914-1915) (TEL Tempo, Espaço e Linguagem, 2025)
This article aims to present information obtained by the Brazilian military attaché on the level of development of the Argentine Armed Forces. This reflection is an integral part of the current postdoctoral research at the Institute of Strategic Studies of the Fluminense Federal University, which deals with the study of aspects of Brazilian Defense Policy, more precisely on the implementation of air units in the southern portions of the Brazilian territory in the 1920s. This theme is part of the process of modernization of the Brazilian land force with the support of the French Military Mission. To this end, we will use the report presented to the General Staff of the Brazilian Army by artillery captain Genserico de Vasconcellos, who was a member of the Brazilian Legation in Buenos Aires between 1914 and 1915. We are dealing with a type of source that has not been properly used in studies dedicated to Military History and the History of Brazilian International Relations in the Old Republic.